ATF3 prevents retinal ganglion cell apoptosis and mitigates microglia-mediated neuroinflammation in retinal ischemia–reperfusion injury - Zhang, Ningzhi; Tian, Tian; Wang, Zhiyi; He, Xuejun; Cao, Wenye; Zhang, Wenxi; Xing, Yiqiao; Yang, Ning (Frontiers in Immunology, 2025)
IntroductionNeuroinflammation is a key pathological response involved in secondary optic nerve injury following retinal ischemia–reperfusion injury. The expression of activating transcription factor 3 (ATF3), a highly conserved protein, is rapidly induced post-injury and is crucial for regulating immunity and inflammation. The potential neuroprotective mechanisms, function, and therapeutic potential of ATF3 following retinal ischemia–reperfusion remain largely unexplored. In this study, we examined the expression and distribution of ATF3 and achieved the overexpression of ATF3 in mouse retina via injection of adeno-associated virus vectors.MethodsRetinal ganglion cell survival was assessed using immunofluorescence staining and terminal deoxynucleotidyl transferase dUTP nick-end labeling assay. Activation status and polarization of microglia and microglia-associated neuroinflammation were also evaluated. In addition, peripheral venous blood samples and aqueous humor were collected from 20 individuals, 10 patients with primary angle-closure glaucoma and 10 controls, to detect changes in ATF3 expression.ResultsATF3 overexpression partially suppressed retinal ganglion cell apoptosis by activating the p-Akt pathway, inhibited microglial activation, reversed microglial M1/M2 polarization, and reduced the release of inflammatory factors by decreasing integrin CD11b expression. ATF3 overexpression improved retinal structure and function by regulating microglial behavior and decreased neuronal death post-retinal ischemia–reperfusion.DiscussionATF3 overexpression may be a potential therapeutic strategy for the management of retinal ischemia–reperfusion-associated neurodegenerative diseases.